Essentials of family medicine - Sloane, Philip D. (Wolters Kluwer / Lippincott Williams, 2012)
"Perhaps more remarkable is how much hasn't changed in the past quarter century. The patient-centered encounter remains the backbone of effective care, whether in the office, on the telephone or orline. In these encounters, attentiveness to the interaction between biological, sosioeconomics, and psychological factors is as crucial and relevant as ever. Family medicine residency programs continue to provide excellent preparation for physicians interested in caring for individuals of all ages and their families within a broad range of practicesettings, styles, and populations. Primary medical care continues to be recognized as the cornerstone of an effective health care system, although integration of primary care into the broader US system remains far from ideal" -- Provided by publisher